Metabolism of immunoglobulin A, lymphocyte function, and histocompatibility antigens in patients on anticonvulsants. Issue 4 (April 1978) - Shakir, R A; Behan, P O; Dick, H; Lambie, D G
Abstract : Low serum IgA levels were found in patients taking phenytoin, together with evidence of depressed T cell function. There was no correlation between the dose or the serum level. A correlation was found, however, with HL-A status, patients with a low IgA showing increased frequency of HL-A2. It is suggested that epileptic patients with HL-A2 status are likely to develop IgA deficiency when given phenytoin.